Mechanism of Bushen Huoxue Recipe on Improving Arterial Calcification in Rats with Osteoporosis Based on OPG/RANKL Signaling Pathway - LIN Xiaorong; YANG Na; ZHENG Bei; ZHAO Hu; XU Junxia (康复学报)
ObjectiveTo observe the effect of Bushen Huoxue Recipe on thoracic aortic calcification and explore the possible mechanism of improving arterial calcification by Bushen Huoxue Recipe based on osteoprotegerin / receptor activator for nuclear factor-κB ligand (OPG/RANKL) signaling pathway in rat model of osteoporosis.MethodsA total of 32 seven-month-old male SD rats were randomly divided into control group, sham operation group, osteoporosis group and Bushen Huoxue group, with eight rats in each group. The control group did not receive any intervention, the sham operation group exposed but did not remove the testicles, and the other two groups removed bilateral testicles to establish the model of osteoporosis. The intervention began at the 16th week after operation. The Bushen Huoxue group was given 55 g/(kg·d) Bushen Huoxue Recipe by gavage, and the other three groups were given the same amount of normal saline, once a day, lasting for eight weeks. Dual-energy X-ray absorptiometry was used to measure the bone mass density (BMD) of femoral shaft of right hindlimb; alizarin red staining was used to detect integrated optical density (IOD) of calcification deposition on the vascular wall of thoracic aorta, and the calcification degree of thoracic aorta was observed; ELISA method was used to detect serum levels of PⅠNP, BGP and CTX-Ⅰ; immunohistochemical staining was used to detect the expression of OPG and RANKL proteins in thoracic aorta.Results1) BMD and IOD value of thoracic aorta calcification deposition: compared with the control group, there were no significant changes of BMD and IOD value in thoracic aorta calcification deposition of the sham operation group (P>0.05), while the BMD of the osteoporosis group decreased significantly, and the IOD value of thoracic aorta calcification deposition increased significantly (P<0.05). Compared with the osteoporosis group, the BMD of the Bushen Huoxue group increased significantly, and IOD value of thoracic aorta calcification deposition decreased significantly, the difference was statistically significant (P<0.05). 2) The level of PⅠNP, BGP and CTX-Ⅰ in the serum: compared with the control group, the level of PⅠNP and BGP of the osteoporosis group decreased significantly, the level of CTX-Ⅰ, a bone resorption marker increased significantly, the difference was statistically significant (P<0.05). Compared with the osteoporosis group, the level of PⅠNP and BGP in the Bushen Huoxue group increased significantly (P<0.05), and there was no significant difference in CTX-Ⅰ level (P>0.05). 3) The expression level of OPG and RANKL protein in thoracic aorta: compared with the control group, the expression level of OPG in the osteoporosis group decreased significantly while the expression level of RANKL increased significantly, the difference was statistically significant (P<0.05); compared with the osteoporosis group, the expression level of OPG protein in thoracic aorta of the Bushen Huoxue group increased significantly, and the expression level of RANKL protein decreased significantly, the difference was statistically significant (P<0.05).ConclusionBushen Huoxue Recipe can improve BMD of osteoporosis rats, promote bone formation, and improve the condition of artery calcification induced by osteoporosis. The possible mechanism may be related to regulating the expression of OPG/RANKL signaling pathway through up-regulation of OPG expression and down-regulation of RANKL expression in thoracic aorta.